Peningkatan keterampilan membaca pemahaman melalui model pembelajaran connecting organizing reflecting extending (core) pada peserta didik kelas iv sekolah dasar - Fitri Wulandari; Rukayah Rukayah; Sularmi Sularmi (Didaktika Dwija Indria, 2019)
The purpose of this study is to improve reading comprehension skills with the Connecting Organizing Reflecting Extending (CORE) learning model. This type of research was classroom action research. This research carried out for two-cycle with each cycle consisting of four activities that are planning, implementation, observation, and reflection. The techniques used to collect data in this study include observation, interviews, tests, and documentation. The data validity techniques used were instrument content validity, source triangulation, and technique triangulation. Data analysis in this study uses comparative descriptive analysis techniques and interactive data analysis. The results of research that have been carried out at the pre-action stage, the class average is 45.69 with classical completeness is 14.29%. The class average increased in the cycle I with an average grade is 68.25 and classical completeness 57.14%, then increased again in cycle II with an average class 79.30 and classical completeness 85.71%. Based on the research results, it can be seen that the application of the Connecting Organizing Reflecting Extending (CORE) learning model can improve reading comprehension skills on the fourth-grade students of the elementary school of Banyurip academic year 2018/2019.